English English - Hubert Fernaldy; Maharani Dian Permanasari; Michael Nicklas (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
The main emphasis of this Point of Sales terminal design is the product should provide easier Cashless payment methods, building trust while operating the terminal and accessible to all group users. A few interests which will shape the design’s outline, this includes the interactions between the seller with the customer and possible self-service payment for disadvantaged groups. The new design will improve the quality of common POS Terminal in markets such as the visual identity, features and usability while trying to increase the user’s trust and payment privacy.